Design of Limb Cooling Tourniquet to Prevent Amputation due to Ischemia - Mhetre, Ketan Sunil (My University, 2019)
During a medevac response, tourniquets are often used as an effective device to mitigate blood loss in incidents involving serious injuries with bleeding. In emergent situations, often involving the transportation of the patient to a medical facility, the prevention of blood loss is prioritized by first responders. Thus, making the use of a tourniquet imperative. Although the device can prevent blood loss from the affected region, the process, however, leads to a deficiency in supplying oxygen which can often result in nerve and tissue damage. Several studies have shown that cooling the limb slows down the metabolism rate and might save a limb from possible amputation. This thesis discusses the process of developing a new limb cooling tourniquet, which consists of a cooling sleeve and an air splint coupled with a conventional tourniquet. To verify the efficiency of the newly developed cooling sleeve, a thermal phantom of a human leg was developed. Its performance was validated with the help of thermal simulation of human limb model. Animal limb cooling experiments were performed at Harborview Medical Center to study the effects of reduced blood flow and oxygen deficiency (ischemia) and the temperature profiles that were obtained as a result of this experiment were compared with the thermal simulation of an animal limb model and the simulations were validated.
Thesis (Master's)--University of Washington, 2019
Keywords: Acute Limb Ischemia; Limb Amputation; Medical Devices; Thermal Simulation of limb; Tourniquet; Mechanical engineering; Mechanical engineering